Alimentasi Anak yang Lahir Lima Bulan Setelah Pernikahan Ibunya dalam Perspektif Mazhab Syafii - Budianna, Fikrina Aliya; Arifin, Muhamad (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
Nafkah is the essential effort to provide for the needs of dependents, encompassing food, clothing, shelter, and other essentials. Scholarly consensus dictates that fulfilling hifdzu an-nafs (preservation of life) entails the responsibility to offer maintenance for those in need, such as a father's duty to support his child. In Indonesian law, legitimate and illegitimate children (ALK) are governed by distinct provisions within the Marriage Law (UUP) and Indonesian Civil Code (KUHPer). This study scrutinizes the considerations and arguments deliberated by the Mataram Religious Court in decision number 401/PA.Mtr/2022/Pd.t. to ascertain their congruence with the Syafii school of thought. Employing qualitative methods, particularly a literature review, the research affirms that the Panel of Judges' six considerations in this case were in line with the Syafii school of thought.